Pengaruh Penerapan Reminiscence Therapy Terhadap Tingkat Depresi Pada Lansia - trevia, reni; Ira Sri Budiarti; Firda Damba Wahyuni; Neneng Rani Hasanah (Jurnal Amanah Kesehatan, 2025)
Elderly as the final stage of the life cycle is often marked by conditions that are not in accordance with expectations, so that many experience depression. World Health Organization states that about 61.6% of the elderly experience depression. The prevalence of depression in the elderly in West Sumatra is 8.8% and 40% are in nursing homes. One of the non-pharmacological therapies is reminiscence therapy. This study aims to determine the effect of implementing reminiscence therapy on the level of depression in the elderly at PSTW Sabai Nan Aluih Sicincin in 2023. This type of research is a Quasi experiment with a pre-test and post-test group approach. This research was conducted at PSTW Sabai Nan Aluih Sicincin. This research was conducted from March to August 2023. The population was 110 elderly people and the sample was 10 elderly people with Purposive Sampling. The research instrument to measure the level of depression used the Geriatric Depression Scale (GDS). The results of the univariate study were obtained before reminiscence therapy, the level of depression in the elderly was 80.0% experiencing mild depression and 20.0% experiencing moderate depression. While after reminiscence therapy, the level of depression in the elderly was 20.0% experiencing mild depression and 80.0% in the normal range. The results of the bivariate study Data analysis using the t-test test, the value of α ≤ 0.05. The results of the study obtained a p value <α with the results of the pre-test and post-test calculations, the p value = 0.000. The results showed that there was a significant difference between the level of depression before and after reminiscence therapy. The conclusion of this study is that there is an influence between reminiscence therapy on the level of depression in the elderly at the Sabai Nan Aluih Sicincin PSTW in 2023. It is recommended to the head of the PSTW that reminiscence therapy can be one of the programs in overcoming depression in the elderly. Keywords: depression; elderly; reminiscence therapy